Estudo traceológico de fósseis de preguiças terrícolas em Santa Elina (MT): implicações sobre paleoecologia e interação ser humano/megafauna no Brasil - Pansani, Thaís Rabito (2023)
The Santa Elina rock shelter, in Mato Grosso State, Central Brazil, stands out as a pivotal zooarchaeological site in the study of the prehistory of South America, especially on the debate on the peopling of the Americas. Its successive human occupations dating from the late Pleistocene to the early Holocene exhibit lithic industry, rock painting, an exceptional abundance of ground sloth bone remains and cultural ornaments from different periods. Although the material culture of Santa Elina has been extensively explored, its paleontological potential have remained poorly investigated. This thesis aimed to provide an in-depth investigation of several aspects of the giant ground sloth from Santa Elina, including updating its taxonomy, new paleoecological inferences, natural aspects of their dermal bones (osteoderms), and their association with prehistoric human occupation, evidenced by the modification and use of osteoderms as personal ornaments during the Last Glacial Maximum (LMG). For this purpose, several traditional and advanced techniques were applied to study the bones and teeth of the ground sloth from Santa Elina. Diverse techniques (Carbon and oxygen stable isotopes analysis, Radiocarbon dating, Stereomicroscopy, Scanning Electron Microscopy, Energy Dispersive Spectroscopy, Photoluminescence, and synchrotron-based Computerized Microtomography, X-Ray Fluorescence and X-Ray Diffraction) were applied to the study of 22 fossil samples. The first paper resulting from this thesis updates the taxonomic status of the mylodontid from Santa Elina, explores its isotopic paleoecology, and provides new radiocarbon dating from dental fragments from units II2 and III4. This study reveals the generalist diet of Glossotherium phoenesis with preference for C4 grasses and reinforces the stratigraphy of unit III4 to the LGM. The second paper explores the human modification of giant sloth bones in Santa Elina during the LGM. This paper provides solid evidence for human manufacturing and use-wear of these artifacts as personal objects during the Ice Age. Finally, the third paper presents preliminary results on paleobiological aspects of natural osteoderms of the mylodontid from Santa Elina. In sum, this thesis contributes to paleoecological and paleobiological aspects of the tropical giant sloth G. phoenesis, as well as to the Zooarchaeology and the Pleistocene occupation of the Americas. The core of this thesis reinforces the co-existence and interaction of prehistoric human populations with the Pleistocene megafauna during the LGM in Brazil, feeding the feverous discussion on the early human settlements in South America.